Microbial Synthesis of Myrcene by Metabolically Engineered Escherichia coil - Kim, Eun-Mi; Eom, Jin-Hee; Um, Youngsoon; Kim, Yunje; Woo, Han Min (American Chemical Society, 2015)
Myrcene, a monoterpene (C-10), has gathered attention as a starting material for high-value compounds, such as geraniol/linalool and (-)-menthol. Metabolic engineering has been successfully applied to produce monoterpenes, such as pinene and limonene, at high levels in microbial hosts. However, microbial synthesis of myrcene has not yet been reported. Thus, we metabolically engineered Escherichia coli for production of myrcene by introducing a heterologous mevalonate pathway and overexpressing tailoring enzymes, such as geranyl diphosphate synthase (GPPS) and myrcene synthase (MS). Although MSs have broad ranges of functionality for producing various monoterpenes, our engineered E. coli strains harboring MS from Quercus ilex L. produced only myrcene (1.67 +/- 0.029 mg/L). Subsequent engineering resulted in higher production of myrcene by optimizing the levels of GPPS in amino-acid-enriched (EZ-rich) defined medium, where glycerol as a carbon source was used. The production level of myrcene (58.19 +/- 12.13 mg/L) was enhanced by 34-fold using in situ two-phase extraction to eliminate cellular toxicity and the evaporation of myrcene.